Correlation between Self-Citation and Impact Factor in Iranian English Medical Journals in WoS and ISC: A Comparative Ap-proach - Seyed Javad GHAZI MIRSAEID; Nadia MOTAMEDI; Nahid RAMEZAN GHORBANI (Tehran University of Medical Sciences, 2015)
Background: In this study, the impact of self-citation (Journal and Author) on impact factor of Iranian English Medical journals in two international citation databases, Web of Science (WoS) and Islamic world science citation center (ISC), were compared by citation analysis. Methods: Twelve journals in WoS and 26 journals in ISC databases indexed between the years (2006-2009) were selected and compared. For comparison of self-citation rate in two databases, we used Wilcoxon and Mann-whitney tests. We used Pearson test for correlation of self-citation and IF in WoS, and the Spearman's correlation coefficient for the ISC database.  Covariance analysis was used for comparison of two correlation tests. P. value was 0.05 in all of tests. Results: There was no significant difference between self-citation rates in two databases (P>0.05). Findings also showed no significant difference between the correlation of Journal self-citation and impact factor in two databases (P=0.526) however, there was significant difference between the author's self-citation and impact factor in these databases (P<0.001). Conclusion: The impact of Author's self-citation in the Impact Factor of WoS was higher than the ISC.